2020
DOI: 10.1016/j.jse.2020.03.011
|View full text |Cite
|
Sign up to set email alerts
|

“Suspension bridge” external fixation technique for the treatment of proximal humeral fractures

Abstract: Background: The purpose of this study was to investigate the clinical efficacy of the ''suspension bridge'' external fixation technique for the treatment of proximal humeral fractures with or without soft tissue defects and infection, as well as postoperative revision. Methods: From August 2013 to June 2018, 9 patients with proximal humeral fractures were selected. There were 5 males and 4 females, with an average age of 55.2 years (range: 32-74 years). Five patients were diagnosed with acute fractures (soft t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A limited report from Tunisia of 58 humeral pseudarthroses showed that effective union was achieved with a no-touch compression technique via monolateral external fixation 52 . Zhao et al reported on 9 cases of a suspension-bridge circular fixator construct for proximal humeral nonunions with skin defects, involving a single diaphyseal ring and multiple oblique olive wires for the fixation of 2, 3, or 4-part fractures 53 . Fifty-four humeral lengthenings were reported by Arenas-Miquelez et al, describing monolateral frame use, proximal-third corticotomies, and a mean lengthening of 9 cm with high satisfaction but 3 patients with resultant elbow flexion contractures 54 .…”
Section: Upper Limbmentioning
confidence: 99%
“…A limited report from Tunisia of 58 humeral pseudarthroses showed that effective union was achieved with a no-touch compression technique via monolateral external fixation 52 . Zhao et al reported on 9 cases of a suspension-bridge circular fixator construct for proximal humeral nonunions with skin defects, involving a single diaphyseal ring and multiple oblique olive wires for the fixation of 2, 3, or 4-part fractures 53 . Fifty-four humeral lengthenings were reported by Arenas-Miquelez et al, describing monolateral frame use, proximal-third corticotomies, and a mean lengthening of 9 cm with high satisfaction but 3 patients with resultant elbow flexion contractures 54 .…”
Section: Upper Limbmentioning
confidence: 99%
“…With semi-rigid implants like the Humerus-Block [6-9], Humerus-Block NG [10] and Button-Fix [11] (all DePuy Synthes, Solothurn, CH), an attempt was made to overcome over-stiffening of the fracture xation. Several studies have described the use of external xation as a semi-rigid, minimally invasive alternative for proximal humerus fracture xation using a variety of systems and surgical techniques [12][13][14][15]. However, the extent to which these techniques can provide a standardized, safe, and reliable solution for the xation of proximal humerus fractures remains unclear.…”
Section: Introductionmentioning
confidence: 99%